Tracking the dissolution behavior of zinc oxide nanoparticles in skimmed milk powder solutions. (15th December 2021) - Tan, Zhiqiang; Chen, Qiang; Yin, Yongguang; Liu, Yanwanjing; Lin, Yaohui; Bai, Qingsheng; Wu, Mengxin; Yao, Weirong; Xu, Shuxia; Liu, Jingfu
Highlights: Characterization of ZnO NPs and Zn(II) ions was achieved by the HF5-based method. Dissolution of ZnO NPs in milk powder solutions was time- and temperature-dependent. Proteins in milk powder had a promoting effect on the dissolution of ZnO NPs. The amount of dissolved Zn(II) ions in milk powder solutions were significantly high. Abstract: Zinc oxide nanoparticles (ZnO NPs) are recently recommended as food additives owing to their outstanding nutritive function. Therefore, understanding their comprehensive information and stability in food samples is highly necessitated. However, the characterization of ZnO NPs in the complex food matrices remains a great challenge, limiting an in-depth understanding of their transformation during food storage. In this study, the hollow fiber flow field-flow fractionation was combined with UV–Vis absorption spectroscopy and inductively coupled plasma optical emission spectroscopy to assess the dissolution behaviors of ZnO NPs in skimmed milk powder solutions by monitoring the changes in the residual ZnO NPs and the amount of dissolved Zn(II) ions. The simultaneous characterization of these two Zn species in skimmed milk powder solutions was achieved without the need for tedious sample pretreatments, and the dissolution of ZnO NPs in skimmed milk powder solutions had time- and temperature-dependent behaviors.